An investigation of the protective effect of alpha+‐thalassaemia against severe Plasmodium falciparum amongst children in Kumasi, Ghana. (10th July 2013) - Opoku‐Okrah, C.; Gordge, M.; Kweku Nakua, E.; Abgenyega, T.; Parry, M.; Robertson, C.; Smith, C. L.
Summary Introduction Several factors influence the severity of Plasmodium falciparum; here, we investigate the impact of alpha+‐thalassaemia genotype on P. falciparum parasitemia and prevalence of severe anaemia amongst microcytic children from Kumasi, Ghana. Methods Seven hundred and thirty‐two children (≤10 years) with P. falciparum were categorised into normocytic and microcytic (mean cell volume ≤76 fL). Microcytic individuals were genotyped for the −α3.7deletional thalassaemia mutation and parasite densities determined. Results Amongst microcytic patients both parasite densities and prevalence of severe malaria parasitemia (≥100 000/μL) were significantly lower (P < 0.001) in the presence of an alpha+‐thalassaemia genotype compared with non‐alpha+‐thalassaemia genotype. There was no evidence that alpha+‐thalassaemia protected against severe anaemia. The protection conferred by alpha‐thalassaemia genotype against severe P. falciparum parasitemia did not change with increasing age. Conclusion The severity of P. falciparum parasitemia was significantly lower in both the homozygous and heterozygous alpha+‐thalassaemia groups compared with microcytic individuals with non‐alpha+‐thalassaemia genotype. The protective effect, from severe malaria, of the alpha+‐thalassaemia allele does not alter with age.